Smart Monitoring System Pada Pembudidayaan Jamur Tiram Menggunakan Metode Fuzzy Logic - Basirun, Arif Reza; Anggraini, Violita; Al Kautsar, Muhammad Nurudduja (nter of Execellence (COE) ICT Infrastructure, Smart Manufacture and Digital Supply Chain, 2024)
Mushrooms, which are known as food commodities, when cultivated require temperatures between 22-28°C and humidity of 60-80%. Controlling these two factors is very crucial, especially when weather fluctuations occur throughout the day. As a solution, an artificial intelligence-based system was introduced to regulate temperature and humidity. The